The Blair identity : Leadership and foreign policy - Dyson, Stephen Benedict (Book collections on Project MUSE., 2009)
Why did Tony Blair take Britain to war with Iraq? Because, this book argues, he was following the core political beliefs and style - the Blair identity - manifest and consistent throughout his decade in power. Kosovo, Sierra Leone, Afghanistan, and finally Iraq were wars to which Blair was drawn due to his black-and-white framing of the world, his overwhelming confidence that he could shape events, and his tightly-held, presidential style of government. In this new application of political psychology to the British prime ministership, Dyson analyses every answer Blair gave to a foreign policy.